2021
DOI: 10.1186/s40795-021-00486-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dietary diversity and nutritional support for children living with HIV in the IeDEA pediatric West African cohort: a non-comparative, feasibility study

Abstract: Background Nutritional care is not optimally integrated into pediatric HIV care in sub-Saharan Africa. We assessed the 6-month effect of a nutritional support provided to children living with HIV, followed in a multicentric cohort in West Africa. Methods In 2014-2016, a nutritional intervention was carried out for children living with HIV, aged under 10 years, receiving antiretroviral therapy (ART) or not, in five HIV pediatric cohorts, in Benin, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…These results are in agreement with the findings of other studies in Africa. 34,35 Statistically significant improvements in weight gain over the 24-month research period and at each six-month follow-up visit since ART was initiated was observed. Although the focus was on changes in WAZ, there was consistent improvement in both WAZ and L/HAZ, with more rapid increases in weight as opposed to gradual increases in length or height.…”
Section: Discussionmentioning
confidence: 92%
“…These results are in agreement with the findings of other studies in Africa. 34,35 Statistically significant improvements in weight gain over the 24-month research period and at each six-month follow-up visit since ART was initiated was observed. Although the focus was on changes in WAZ, there was consistent improvement in both WAZ and L/HAZ, with more rapid increases in weight as opposed to gradual increases in length or height.…”
Section: Discussionmentioning
confidence: 92%